Preparation of peanut shell nitrogen-doped carbon-supported copper catalyst and its application in the synthesis of diethyl carbonate

By using peanut chitin nitrogen doped with carbon-supported copper catalyst, the problem of poor activity and stability of carbon-supported copper catalysts under high temperature and high pressure conditions was solved, and efficient diethyl carbonate synthesis was achieved, and the catalytic performance was significantly improved.

CN116673054BActive Publication Date: 2024-12-17TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310650517.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-04
Publication Date
2024-12-17
Estimated Expiration
2043-06-04

AI Technical Summary

Technical Problem

The existing carbon-supported copper-based catalysts are prone to loss, agglomeration and oxidation of copper species on the surface of the catalyst under high temperature, high pressure and rapid stirring conditions, which affects its activity and stability, and hinders its synthesis of diethyl carbonate in ethanol oxidation carbonyl synthesis. Application.

Method used

Using peanut chitin nitrogen-doped carbon as a support, carbon-supported copper catalysts with microporous and mesoporous structures were prepared by hydrothermal carbonization and copyrolysis. The pore structure is adjusted by nitrogen doping and providing electronic effects to improve copper nanoparticles. dispersion and antioxidant capacity.

Benefits of technology

The activity and stability of the catalyst are significantly improved, and the catalytic performance is 6 times higher than the space-time yield of traditional carbon-supported copper catalysts, solving the problems of copper agglomeration and oxidation, and achieving efficient diethyl carbonate synthesis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116673054B_ABST
    Figure CN116673054B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of catalyst preparation, and in particular to the preparation of a peanut shell nitrogen-doped carbon-supported copper catalyst and its application in the synthesis of diethyl carbonate. The present invention adopts peanut shell as a raw material, and prepares a biomass carbon carrier by hydrothermal carbonization and co-pyrolysis. The raw material cost is low and it complies with the chemical principle of green and low carbon. Nitrogen is doped to adjust the composition and distribution of the pore structure. The prepared peanut shell nitrogen-doped carbon-supported copper catalyst has a pore structure with coexistence of micropores and mesopores, and a specific surface area of ​​up to 2731 m 2 •g ‑1 The surface of the carrier is rich in carbon defects and oxygen-containing functional groups, which is conducive to providing more active sites to anchor copper nanoparticles, thereby improving the dispersion of copper species and improving catalytic activity and stability. At the same time, the electron donation effect of N increases the Cu content in the catalyst. 0 and Cu + The generation and antioxidant capacity of the catalyst further improved the yield and activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalyst preparation, and in particular to the preparation of a peanut shell nitrogen-doped carbon-supported copper catalyst and application thereof in the synthesis of diethyl carbonate. Background Art

[0002] As an important green and environmentally friendly raw material, diethyl carbonate (DEC) has been widely used due to its excellent biodegradability, low toxicity, good solubility and other advantages. Among the many DEC synthesis processes, the ethanol oxidative carbonylation method has become a hot topic of research at home and abroad in recent years due to its low production cost, high product selectivity, and environmental friendliness. At present, the main catalyst used in this process is a carbon-supported copper-based catalyst. However, since the reaction is carried out under high temperature, high pressure and rapid stirring conditions, the copper species on the catalyst surface are prone to loss, agglomeration and oxidation, which seriously affects the activity and stability of this type of catalyst and hinders its industrialization process. Therefore, controlling the size and dispersion of copper nanoparticles has become a key issue that needs to be improved in the catalyst design and preparation process.

[0003] In recent years, biochar has attracted people's interest due to its advantages such as renewability, adjustable surface properties, and green and low cost. 2 / g) activated carbon has been widely used in the field of electrochemistry. Peanut shell carbon has been widely used due to its high specific surface area and exhibits excellent electrochemical performance, but there are few reports on its use in the oxidative carbonylation of ethanol to synthesize DEC. Summary of the invention

[0004] In order to solve the problem that copper species on the catalyst surface of the current carbon-supported copper-based catalyst are easily lost, agglomerated and oxidized, the present invention provides a preparation method of a peanut shell nitrogen-doped carbon-supported copper catalyst and its application in the synthesis of diethyl carbonate.

[0005] The present invention is achieved through the following technical scheme: a green high-yield peanut shell nitrogen-doped carbon-supported copper catalyst is prepared, comprising the following steps:

[0006] (1) Preparation of peanut shell nitrogen-doped carbon:

[0007] After the raw peanut shell powder is carbonized at 180°C for 6 hours, melamine, the carbonized peanut shell powder and potassium hydroxide are fully stirred with water until they are evenly mixed, the obtained mixed solution is dried, and the dried solid is heated to 800°C under an inert atmosphere and maintained for 2 hours, and then naturally cooled to room temperature to obtain a black solid; the black solid is washed with HCl solution, filtered until the filtrate is neutral, the filter residue is collected, dried, and fully ground to obtain a peanut shell nitrogen-doped carbon carrier;

[0008] (2) Preparation of peanut shell nitrogen-doped carbon-supported copper catalyst:

[0009] A peanut shell nitrogen-doped carbon carrier was fully wetted with a copper nitrate aqueous solution, and after ultrasonic treatment, the water on the surface of the carrier was evaporated by stirring at 80°C, and then dried to obtain a peanut shell nitrogen-doped carbon-supported copper salt precursor; the peanut shell nitrogen-doped carbon-supported copper salt precursor was placed in a nitrogen and hydrogen mixed gas atmosphere, and calcined at 400°C for 2h to obtain a peanut shell nitrogen-doped carbon-supported copper catalyst.

[0010] As a further improvement of the preparation technology scheme of the present invention, in step (1), the mass ratio of melamine, carbonized peanut shell powder and potassium hydroxide is 0.5-2:1:2.

[0011] As a further improvement of the preparation technical solution of the present invention, in step (2), the mass ratio of the copper nitrate, water and the peanut shell nitrogen-doped carbon carrier is 1:71.1:2.37.

[0012] As a further improvement of the preparation technology scheme of the present invention, in step (2), the temperature of the ultrasonic treatment is room temperature and the treatment time is 0.5 h.

[0013] The present invention further provides the use of the peanut shell nitrogen-doped carbon-supported copper catalyst obtained by the preparation of the green high-yield peanut shell nitrogen-doped carbon-supported copper catalyst in the synthesis of DEC by oxidative carbonylation of ethanol.

[0014] As a further improvement of the application technical solution of the present invention, the application method is: peanut shell nitrogen-doped carbon-loaded copper catalyst and ethanol are placed in a closed reaction kettle, carbon monoxide is filled in and released, and the process is repeated three times to replace the air in the kettle. After the air is emptied, oxygen and carbon monoxide are filled in sequence, and the temperature is raised to carry out the DEC reaction.

[0015] As a further improvement of the application technical solution of the present invention, when oxygen and carbon monoxide are charged in sequence, the molar ratio of carbon monoxide to oxygen in the kettle is 20-29:1-10.

[0016] As a further improvement of the application technical solution of the present invention, the reaction temperature of the DEC reaction is 90-130° C., and the reaction time is 60 min.

[0017] The preparation and application of the green high-yield peanut shell nitrogen-doped carbon-supported copper catalyst provided by the present invention has the following advantages compared with the prior art:

[0018] The present invention prepares a new carbon carrier with ultra-high specific surface area. The peanut shell is used as a raw material, and the biomass carbon carrier is prepared by hydrothermal carbonization and co-pyrolysis. The raw material cost is low and it conforms to the chemical principle of green and low carbon. The carbon carrier is nitrogen-doped to adjust the composition and distribution of the pore structure. The prepared peanut shell nitrogen-doped carbon-loaded copper catalyst has a pore structure with coexistence of micropores and mesopores, and the specific surface area is as high as 2731m 2 ·g -1 The surface of the carrier is rich in carbon defects and oxygen-containing functional groups, which is conducive to providing more active sites to anchor copper nanoparticles, thereby improving the dispersion of copper species and improving catalytic activity and stability. At the same time, the electron donation effect of N increases the Cu content in the catalyst. 0 and Cu + The generation and antioxidant capacity of peanut shell carbon support further improve the yield and activity of the catalyst. In short, the synergistic effect of ultra-high specific surface area peanut shell carbon support and nitrogen doping fundamentally solves the problems of copper agglomeration and oxidation. Compared with the catalytic performance of carbon-supported copper catalysts reported in the literature, the space-time yield of DEC is about 6 times that of Cu / AC catalysts reported in the literature. Therefore, the prepared peanut shell nitrogen-doped carbon-supported copper catalyst is an efficient catalyst for the synthesis of DEC by ethanol oxidative carbonylation. In the DEC synthesis reaction process, it provides more anchoring sites for active metals and achieves high dispersion of Cu nanoparticles, fundamentally solving the problems of low activity and poor stability existing in current catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0021] Figure 1 This is the N2 adsorption and desorption characterization of the catalyst Cu / PSAC-N1 prepared in Example 1 of the present invention. The catalyst in the figure presents type I and IV composite isotherms, indicating that the catalyst has a porous structure with both micropores and mesopores.

[0022] Figure 2 The SEM images of PSAC (a) prepared in the comparative example and PSAC-N1 (b) prepared in Example 1 of the present invention show that both PSAC and PSAC-N1 present a connected two-dimensional network porous structure. Many small protrusions appear in the nitrogen-doped PSAC-N1, which increases the specific surface area and surface carbon defects of the carrier.

[0023] Figure 3 This is the TEM image of the catalyst in Example 1 of the present invention. It can be clearly observed that Cu NPs are uniformly dispersed on the surface of the carbon support, and the grain size of Cu is 10.1 nm, which is significantly smaller than the grain size of Cu in the comparative example (21.6 nm).

[0024] Figure 4 The catalytic performance of DEC synthesized by catalysis in Example 1 of the present invention is studied. It can be seen from the figure that Cu / PSAC-N1 exhibits better conversion rate and yield than Cu / PSAC catalyst, that is, the conversion rate is 10.7% and the yield is 3371.3 mg / (g·h). DETAILED DESCRIPTION

[0025] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0026] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.

[0027] The present invention provides a specific embodiment of the preparation of a green high-yield peanut shell nitrogen-doped carbon-supported copper catalyst, comprising the following steps:

[0028] (1) Preparation of peanut shell nitrogen-doped carbon:

[0029] After the raw peanut shell powder is carbonized at 180°C for 6 hours, melamine, the carbonized peanut shell powder and potassium hydroxide are fully stirred with water until they are evenly mixed, the obtained mixed solution is dried, and the dried solid is heated to 800°C under an inert atmosphere and maintained for 2 hours, and then naturally cooled to room temperature to obtain a black solid; the black solid is washed with HCl solution, filtered until the filtrate is neutral, the filter residue is collected, dried, and fully ground to obtain a peanut shell nitrogen-doped carbon carrier;

[0030] (2) Preparation of peanut shell nitrogen-doped carbon-supported copper catalyst:

[0031] A peanut shell nitrogen-doped carbon carrier was fully wetted with a copper nitrate aqueous solution, and after ultrasonic treatment, the water on the surface of the carrier was evaporated by stirring at 80°C, and then dried to obtain a peanut shell nitrogen-doped carbon-supported copper salt precursor; the peanut shell nitrogen-doped carbon-supported copper salt precursor was placed in a nitrogen and hydrogen mixed gas atmosphere, and calcined at 400°C for 2h to obtain a peanut shell nitrogen-doped carbon-supported copper catalyst.

[0032] In the present invention, preferably, the Cu loading in the peanut shell nitrogen-doped carbon-supported copper salt precursor is 10wt%. The catalyst has micropores and mesopores coexisting in the pores, and the Cu nanoparticles are evenly dispersed on the carrier; the surface of the carbon material is rich in defects and oxygen-containing functional groups, which is conducive to providing more active sites to anchor the copper nanoparticles. At the same time, the electron donation effect of N increases the Cu in the catalyst. 0 The generation and antioxidant capacity of the catalyst further improved the activity and stability of the catalyst.

[0033] In one embodiment provided by the present invention, in step (1), the mass ratio of melamine, carbonized peanut shell powder and potassium hydroxide is 0.5-2:1:2.

[0034] In another embodiment provided by the present invention, in step (2), the mass ratio of the copper nitrate, water and the peanut shell nitrogen-doped carbon carrier is 1:71.1:2.37. In the present invention, the water can be distilled water, deionized water, etc.

[0035] In one embodiment provided by the present invention, in step (2), the temperature of the ultrasonic treatment is room temperature, the treatment time is 0.5 h, the ultrasonic radiation power is 500 W, and the ultrasonic frequency is 3000 Hz.

[0036] The present invention also provides a green high-yield peanut shell nitrogen-doped carbon-supported copper catalyst prepared using the peanut shell nitrogen-doped carbon-supported copper catalyst in the synthesis of DEC by oxidative carbonylation of ethanol.

[0037] In one embodiment provided by the present invention, the application method is: peanut shell nitrogen-doped carbon-loaded copper catalyst and ethanol are placed in a closed reaction kettle, carbon monoxide is filled in and released, and the process is repeated three times to replace the air in the kettle. After the air is emptied, oxygen and carbon monoxide are filled in sequence, and the temperature is raised to carry out the DEC reaction.

[0038] Preferably, the mass volume ratio of the peanut shell nitrogen-doped carbon-supported copper catalyst to ethanol is 0.2:10.

[0039] In another embodiment provided by the present invention, when oxygen and carbon monoxide are charged sequentially, the molar ratio of carbon monoxide to oxygen in the kettle is 20-29:1-10.

[0040] In one embodiment provided by the present invention, the reaction temperature of the DEC reaction is 90-130°C, and the reaction time is 60 minutes. Preferably, the reaction temperature can be 90°C, 100°C, 110°C, 120°C, or 130°C.

[0041] The specific embodiments of the present invention are described in detail below.

[0042] Embodiment 1:

[0043] The chemical materials used in this embodiment are: raw peanut shell powder, melamine, potassium hydroxide, copper nitrate, concentrated hydrochloric acid, deionized water, ethanol, nitrogen, hydrogen, carbon monoxide, oxygen, and their combined amounts are as follows: in grams, milliliters, centimeters 3 Is the unit of measurement.

[0044]

[0045]

[0046] Select the above chemical materials: The chemical materials required for preparation should be carefully selected and quality purity controlled:

[0047]

[0048] A preparation and application of peanut shell nitrogen-doped carbon-supported copper Cu / PSAC-N1 catalyst, comprising the following steps:

[0049] (1) Preparation of PSAC-N1

[0050] Weigh 30.00 g ± 0.01 g of raw peanut shell powder, 30.00 g ± 0.01 g of melamine, 60.00 g ± 0.01 g of potassium hydroxide, and 200 ml of water into a beaker and stir thoroughly. Dry the resulting mixed liquid in an oven at 110 °C overnight, place the dried solid in a corundum boat and transfer it to a high-temperature tube furnace and heat it at 5 °C min under a N2 atmosphere. -1 The heating rate was raised to 800°C and kept constant for 2 hours. After cooling to room temperature, a black solid was obtained. The black solid was filtered with 1000 ml of 0.5 M hydrochloric acid solution (prepared with concentrated hydrochloric acid), and then washed with deionized water until the filtrate was neutral. The filter residue was collected, dried and ground into powder to obtain nitrogen-doped peanut shell carbon PSAC-N1.

[0051] (2) Preparation of Cu / PSAC-N1 catalyst

[0052] ① Preparation of PSAC-N1 copper salt precursor

[0053] 0.211 g of copper nitrate was weighed and placed in 15 mL of deionized water. After fully dissolving, it was dropped into a beaker containing 0.5 g of PSAC-N1. After PSAC-N1 was fully wetted, it was ultrasonically treated at 25 ° C for 0.5 h, then stirred in an 80 ° C water bath until the water in the beaker was evaporated, and then dried in an 80 ° C oven for 12 h to obtain a peanut shell nitrogen-doped carbon-supported copper salt precursor with a Cu loading of 10 wt% (10 wt% = m Cu / m Cu +m C ).

[0054] ② Preparation of PSAC-N1 copper-supported catalyst

[0055] The prepared peanut shell nitrogen-doped carbon-supported copper salt precursor was placed in a high-temperature tube furnace and heated at 5°C min-1 in a nitrogen and hydrogen mixed gas atmosphere. -1 The temperature was raised to 400°C and calcined for 2h to obtain a Cu / PSAC-N1 catalyst; the volume ratio of nitrogen to hydrogen in the mixed gas atmosphere was 1:2.

[0056] (3) Ethanol oxidative carbonylation reaction to DEC

[0057] 0.2gCu / PSAC-N1 catalyst and 10mL ethanol were placed in a 50mL micro-autoclave, sealed, replaced with 2Mpa CO, and then filled with gas (CO and O2) with a total pressure of 3Mpa, where the molar ratio of CO and O2 was 5:1. The temperature was raised to 120℃ at 900r / min and the DEC reaction was carried out at a constant temperature for 60min to test the catalytic activity of the catalyst.

[0058] (4) Testing, assaying, analyzing, and characterizing the color, morphology, composition, and chemical and physical properties of samples;

[0059] The specific surface area and pore structure were analyzed by N2 adsorption and desorption characterization;

[0060] The morphology and structure of the catalyst were analyzed using scanning electron microscopy;

[0061] Conclusion: PSAC-N1 is a black powder with a two-dimensional porous carbon structure of both micropores and mesopores.

[0062] (5) The prepared black powder should be stored in a colorless transparent glass container, sealed and placed in a dry, cool and clean environment. It should be waterproof, sun-proof, acid-base and salt-proof. The storage temperature should be 20℃±2℃ and the relative humidity should be ≤10%.

[0063] Comparative Example:

[0064] A preparation method and application of peanut shell carbon supported copper Cu / PSAC catalyst, comprising the following steps:

[0065] (1) Preparation of PSAC

[0066] Weigh 30.00 g ± 0.01 g of raw peanut shell powder, 60.00 g ± 0.01 g of potassium hydroxide, and 200 ml of water into a beaker and stir thoroughly. Dry the resulting mixed liquid in an oven at 110 °C overnight, place the dried solid in a corundum boat and transfer it to a high-temperature tube furnace and heat it at 5 °C min under a N2 atmosphere. -1The temperature was raised to 800°C at a rate of 1000 °C and kept constant for 2 h. After cooling to room temperature, a black solid was obtained. The black solid was filtered with 1000 ml of 0.5 M hydrochloric acid solution and then washed with deionized water until the filtrate was neutral. The filter residue was collected, dried and ground into powder to obtain peanut shell carbon PSAC.

[0067] Steps (2) and (3) are the same as steps (2) and (3) of Example 1, wherein a Cu / PSAC catalyst is obtained in step (2).

[0068] Table 1 is a performance comparison of the Cu / PSAC-N1 catalyst prepared in this example and the carbon-supported copper-based catalyst reported in the literature.

[0069] Table 1

[0070]

[0071]

[0072] It can be seen from the comparison in the above table that the activity and space-time yield of the Cu / PSAC-N1 catalyst prepared by the preparation method of the present invention are better than those of common catalysts.

[0073] Embodiment 2:

[0074] A preparation method and application of a Cu / PSAC-N0.5 catalyst comprises the following steps:

[0075] (1) Weigh 30.00 g ± 0.01 g of raw peanut shell powder, 15.00 g ± 0.01 g of melamine, 60.00 g ± 0.01 g of potassium hydroxide, and 200 ml of water into a beaker and stir thoroughly. Dry the resulting mixed liquid in an oven at 110 °C overnight, place the dried solid in a corundum boat and transfer it to a high-temperature tube furnace and heat it at 5 °C min under a N2 atmosphere. -1 The temperature was raised to 800°C at a rate of 1000 °C and kept constant for 2 h. After cooling to room temperature, a black solid was obtained. The black solid was filtered with 1000 ml of 0.5 M hydrochloric acid solution and then washed with deionized water until the filtrate was neutral. The filter residue was collected, dried and ground into powder to obtain PSAC-N0.5.

[0076] Steps (2) and (3) are the same as steps (2) and (3) of Example 1.

[0077] Embodiment 3:

[0078] A method for preparing a Cu / PSAC-N1.5 catalyst comprises the following steps:

[0079] (1) Weigh 30.00 g ± 0.01 g of raw peanut shell powder, 45.00 g ± 0.01 g of melamine, 60.00 g ± 0.01 g of potassium hydroxide, and 200 ml of water into a beaker and stir thoroughly. Dry the resulting mixed liquid in an oven at 110 °C overnight, place the dried solid in a corundum boat and transfer it to a high-temperature tube furnace and heat it at 5 °C min under a N2 atmosphere. -1 The temperature was raised to 800°C at a rate of 1000 °C and kept constant for 2 h. After cooling to room temperature, a black solid was obtained. The black solid was filtered with 1000 ml of 0.5 M hydrochloric acid solution and then washed with deionized water until the filtrate was neutral. The filter residue was collected, dried and ground into powder to obtain PSAC-N1.5.

[0080] Steps (2) and (3) are the same as steps (2) and (3) of Example 1.

[0081] Table 2 shows the catalytic performance of the catalysts Cu / PSAC-N1, Cu / PSAC-N0.5 and Cu / PSAC-N1.5 prepared in Examples 1, 2 and 3.

[0082] Table 2 Performance comparison of catalysts with different N doping amounts

[0083]

[0084] It can be seen from the table above that the incorporation of N effectively improves the initial activity of the catalyst, and with the increase of N content, the catalytic performance first increases and then decreases, and the best catalytic performance is shown on the Cu / PSAC-N1 catalyst. Among them, Cu / PSAC-N1 has the best catalytic performance, with an EtOH conversion rate of 10.7%, a DEC selectivity of 62.4%, and a space-time yield of 3371.3 mg / (g·h).

[0085] Embodiment 4:

[0086] Based on the same steps (1) and (2) as in Example 1, in step (3), 0.2 g of the catalyst and 10 mL of ethanol were placed in a 50 mL micro-autoclave, which was sealed and replaced with 2 MPa CO. Then, a gas (CO and O2) with a total pressure of 3 MPa was introduced, wherein the molar ratio of CO to O2 was 5:1. The temperature was raised to 90°C at 900 r / min and the DEC reaction was carried out at a constant temperature for 60 min to test the catalytic activity of the catalyst.

[0087] Embodiment 5:

[0088] Based on the same steps (1) and (2) as in Example 1, in step (3), ethanol oxidation carbonylation to DEC reaction, 0.2 g of catalyst and 10 mL of ethanol were placed in a 50 mL micro-autoclave, which was sealed and replaced with 2 MPa CO. Then, a gas (CO and O2) with a total pressure of 3 MPa was introduced, wherein the molar ratio of CO to O2 was 5:1. The temperature was raised to 100°C at 900 r / min and the DEC reaction was carried out at a constant temperature for 60 min to test the catalytic activity of the catalyst.

[0089] Embodiment 6:

[0090] Based on the same steps (1) and (2) as in Example 1, in step (3), 0.2 g of the catalyst and 10 ml of ethanol were placed in a 50 ml micro-autoclave, which was sealed and replaced with 2 MPa CO. Then, a gas (CO and O2) with a total pressure of 3 MPa was introduced, wherein the molar ratio of CO to O2 was 5:1. The temperature was raised to 110°C at 900 r / min and the DEC reaction was carried out at a constant temperature for 60 min to test the catalytic activity of the catalyst.

[0091] Embodiment 7:

[0092] Based on the same steps (1) and (2) as in Example 1, in step (3), 0.2 g of the catalyst and 10 ml of ethanol were placed in a 50 ml micro-autoclave, which was sealed and replaced with 2 MPa CO. Then, a gas (CO and O2) with a total pressure of 3 MPa was introduced, wherein the molar ratio of CO to O2 was 5:1. The temperature was raised to 130°C at 900 r / min and the DEC reaction was carried out at a constant temperature for 60 min to test the catalytic activity of the catalyst.

[0093] Embodiment 8:

[0094] Based on the same steps (1) and (2) as in Example 1, in step (3), 0.2 g of the catalyst and 10 ml of ethanol were placed in a 50 ml micro-autoclave, which was sealed and replaced with 2 MPa CO. Then, a gas (CO and O2) with a total pressure of 3 MPa was introduced, wherein the molar ratio of CO to O2 was 29:1. The temperature was raised to 120°C at 900 r / min and the DEC reaction was carried out at a constant temperature for 60 min to test the catalytic activity of the catalyst.

[0095] Embodiment 9:

[0096] Based on the same steps (1) and (2) as in Example 1, in step (3), 0.2 g of the catalyst and 10 ml of ethanol were placed in a 50 ml micro-autoclave, which was sealed and replaced with 2 MPa CO. Then, a gas (CO and O2) with a total pressure of 3 MPa was introduced, wherein the molar ratio of CO to O2 was 9:1. The temperature was raised to 120°C at 900 r / min and the DEC reaction was carried out at a constant temperature for 60 min to test the catalytic activity of the catalyst.

[0097] Embodiment 10:

[0098] Based on the same steps (1) and (2) as in Example 1, in step (3), 0.2 g of the catalyst and 10 ml of ethanol were placed in a 50 ml micro-autoclave, which was sealed and replaced with 2 MPa CO. Then, a gas (CO and O2) with a total pressure of 3 MPa was introduced, wherein the molar ratio of CO to O2 was 2:1. The temperature was raised to 120°C at 900 r / min and the DEC reaction was carried out at a constant temperature for 60 min to test the catalytic activity of the catalyst.

[0099] The above is only a specific implementation of the present invention, which enables those skilled in the art to understand or implement the present invention. Although detailed descriptions are given with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments, and they should all be covered by the protection scope of the claims.

Claims

1. A green high-yield peanut shell nitrogen-doped carbon-supported copper catalyst preparation, characterized in that: The following steps are involved: (1) Preparation of peanut shell nitrogen-doped carbon: After raw peanut shell powder is carbonized at 180°C for 6 h, melamine, carbonized peanut shell powder and potassium hydroxide are fully stirred with water until they are uniformly mixed, the obtained mixed solution is dried, and the dried solid is heated to 800°C under an inert atmosphere and maintained for 2 h, and then naturally cooled to room temperature to obtain a black solid; the black solid is washed with HCl solution, filtered until the filtrate is neutral, the filter residue is collected, dried and fully ground to obtain a peanut shell nitrogen-doped carbon carrier; in step (1), the mass ratio of melamine, carbonized peanut shell powder and potassium hydroxide is 0.5~2:1:2; (2) Preparation of peanut shell nitrogen-doped carbon-supported copper catalyst: A peanut shell nitrogen-doped carbon carrier is fully wetted with a copper nitrate aqueous solution, and after ultrasonic treatment, the water on the surface of the carrier is evaporated by stirring at 80°C, and then dried to obtain a peanut shell nitrogen-doped carbon-supported copper salt precursor; the peanut shell nitrogen-doped carbon-supported copper salt precursor is placed in a nitrogen and hydrogen mixed gas atmosphere and calcined at 400°C for 2 h to obtain a peanut shell nitrogen-doped carbon-supported copper catalyst; in step (2), the mass ratio of the copper nitrate, water and peanut shell nitrogen-doped carbon carrier is 1:71.1:2.

37.

2. The preparation of a green high-yield peanut shell nitrogen-doped carbon-supported copper catalyst according to claim 1, characterized in that: In step (2), the temperature of the ultrasonic treatment is room temperature and the treatment time is 0.5 h.

3. Use of the peanut shell nitrogen-doped carbon-supported copper catalyst obtained by the preparation of a green high-yield peanut shell nitrogen-doped carbon-supported copper catalyst as described in claims 1 to 2 in the synthesis of DEC by oxidative carbonylation of ethanol.

4. The use according to claim 3, characterized in that: The application method is as follows: peanut shell nitrogen-doped carbon-supported copper catalyst and ethanol are placed in a closed reaction kettle, carbon monoxide is filled in and released, and the process is repeated three times to replace the air in the kettle, and after the air is emptied, oxygen and carbon monoxide are filled in sequence, and the temperature is raised to carry out a DEC reaction.

5. The use according to claim 4, characterized in that: When oxygen and carbon monoxide are charged sequentially, the molar ratio of carbon monoxide to oxygen in the kettle is 20-29:1-10.

6. The use according to claim 4, characterized in that: The reaction temperature of DEC reaction is 90~130 ℃, and the reaction time is 60 min.

Citation Information

Patent Citations

  • Catalyst for synthesizing diethyl carbonate by ethanol vapor-phase carbonyl

    CN101181688A

  • Rapid preparation method and application of active carbon aerogel supported copper catalyst

    CN106076334A

  • Preparation method and application of Cu / N doped carbon nanosheet catalyst with high stability

    CN111974435A

  • Catalyst for synthesizing dimethyl carbonate through methanol oxidative carbonylation, preparation method and application thereof

    CN114602530A

  • Catalyst for efficiently catalyzing oxidative carbonylation of ethanol to prepare diethyl carbonate and preparation method thereof

    CN115518653A